2005
DOI: 10.1585/jspf.81.280
|View full text |Cite
|
Sign up to set email alerts
|

Pedestal Characteristics of H-Mode Plasmas in JT-60U and ASDEX Upgrade

Abstract: The role of the pedestal structure in ELMy H-mode plasmas for the core energy confinement and for the ELM energy losses were investigated in two tokamak-type devices, JT-60U and ASDEX Upgrade. The confinement degradation seen at higher densities is attributed to the reduction of the pedestal temperature limited by the ELM activities and the stiffness of the temperature profiles. In high triangularity or impurity seeded H-modes, in which higher energy confinement is generally achieved, a higher pedestal tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
6
7
0
Order By: Relevance
“…4. This half reduction of ELM energy loss agrees with experimental observations [4,5]. We also do simulations with a low-field-side (LFS) pellet and obtain similar results.…”
Section: Fig 2 Time Evolution Of Background Total Pressure P Profilsupporting
confidence: 89%
See 2 more Smart Citations
“…4. This half reduction of ELM energy loss agrees with experimental observations [4,5]. We also do simulations with a low-field-side (LFS) pellet and obtain similar results.…”
Section: Fig 2 Time Evolution Of Background Total Pressure P Profilsupporting
confidence: 89%
“…The resultant energy loss is less than half of the 'natural' ELMs as shown in figure 5. This reduction of ELM energy loss agrees with experimental observations in ASDEX Upgrade [4,5] and DIII-D [27]. We also performed simulations with a LFS pellet and obtained similar results.…”
Section: Elm Triggered By Pellet Energy Absorptionsupporting
confidence: 87%
See 1 more Smart Citation
“…The values of τ ELM and ped are typical values in experiments [1,5,8]. On the other hand, the value of χ max ELM is chosen to obtain ELM energy and particle losses comparable to JT-60U experiments [3,8]. The other parameters are chosen as puf = 0.3×10 22 s −1 , f dpump = 0.01, f wpump = 0, f dr = 0.02, L r = 0.4 m and T n = 3 eV.…”
Section: Integrated Simulation Resultsmentioning
confidence: 99%
“…The ELM cycle consists of two phases: an ELM crash by the MHD instability inducing energy and particle losses from the pedestal plasma and a quiescent phase recovering the pedestal pressure between ELMs (inter-ELM phase). A multi-machine analysis shows that the ELM energy loss increases with decreasing collisionality [1][2][3] and the inter-ELM transport increases with collisionality [3,4]. Additionally, recent experiments showed that the toroidal rotation and the toroidal field ripple also affects the ELM energy loss [5].…”
Section: Introductionmentioning
confidence: 99%